HUBUNGAN KARAKTERISTIK WIRAUSAHA DENGAN KEBERHASILAN USAHATANI HORTIKULTURA - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Yosini Deliana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
The purpose of this study was to find out how the relationship between entrepreneurial characteristics and the success of Horticulture Farmers in Cibodas Village, Lembang District, West Bandung Regency. This research uses quantitative design with descriptive survey method. The research sample was taken by probability sampling method. Data analysis was carried out descriptively statistically and using Rank Spearman correlation analysis tools. The results showed that the average sample of farmers was male, in productive age, had received a 9-year compulsory education program, and had a business scale of 417.34 Tumbak. Entrepreneurial characteristics possessed by farmers are included in the criteria of "Good" with a percentage of 77.05%, Farming success is included in the criteria of "Good" with a percentage of 77.2%, and the results of the study show there is a positive correlation on all characteristics.